Discreteness of cell-surface contacts affects spatio-temporal dynamics, adhesion, and proliferation of mouse embryonic stem cells - Kimmle, Esther; Haijan Foroushani, Zahra; Keppler, Stephan; Thoma, Judith; Hayashi, Kentaro; Yamamoto, Akihisa; Bastmeyer, Martin; Tanaka, Motomu (Frontiers in physics, 2022)
The self-renewal and lineage-specific differentiation of stem cells are regulated by interactions with their microenvironments, called stem cell niche. Stem cells receive both biochemical and biophysical cues from their niche, which leads to the activation of signaling pathways, resulting in the modulation of gene expressions to guide their fate. Most of previous studies are focused on the effect of substrate stiffness using hydrogels with different Young’s moduli, and information is lacking on the effect of the discreteness of cell-substrate contacts on stem cells. Using mouse pluripotent, embryonic stem cells (mESCs) as the model system for early development, we quantitatively investigated the migration, dynamic deformation, and adhesion of mESCs on sparse and dense gelatin nanofibers deposited on glass surfaces, with a continuous layer of gelatin coated on glass substrates as the control.
Gesehen am 20.01.2022